Dietary supplements consumption among youths in Seremban / Nor Azira Md Radzi, Norazila Abdul Aziz and Nur Farah Azren Mohd Nazeri - Md Radzi, Nor Azira; Abdul Aziz, Norazila; Mohd Nazeri, Nur Farah Azren (2020)
Good nutrition is one of the keys to a healthy life. Currently, many people consume dietary supplements to get their recommended intake of nutrient deficiency. However, the information on their use by sub-population such as youth is scarce. The purpose of this study is to investigate the prevalence of dietary supplements among youths in Seremban, to determine the association of supplements intake status with socio¬ demographic factors and to segment the dietary supplement users based on education level, gender, amount spend for dietary supplements and age. Data were collected from 300 youths in Seremban using administered questionnaires distributed at several shopping malls in Seremban. The prevalence of dietary supplement in this study found that dietary supplements users are "9.7% (119 respondents), the main reasons for consuming supplements are 'maintenance of health' (77.3%), followed by 'enhances energy' (38. 7%). A chi-square test of independence showed that there was an association between supplements intake status with gender, age category, race and monthly income with p-value < .05. Two-step clusters analysis reveals that there are three clusters of users, segmented based on gender, the consumption of dietary supplement , duration taking supplements and, age. Cluster with highest respondent represents female, the consumption of dietary supplements about 1-6 month , duration taking supplements about daily and mean age of 23.76. Results acquired have shown some understanding of the insight regarding dietary supplements usage among youth in Seremban.